HGG-37. PAEDIATRIC GLIOBLASTOMA CELLS SHOW CRITICAL DEPENDENCIES ON EPIGENOMIC AND EPITRANSCRIPTOMIC CONTROL OF GENE EXPRESSION BY H3.3G34R/V MUTATIONS. (4th December 2020) - Bjerke, Lynn; Mackay, Alan; Rogers, Rebecca; Grabovska, Yura; Molinari, Valeria; Temelso, Sara; Cole, Kristina; Waanders, Angela; Carcaboso, Angel Montero; Vinci, Maria; Jones, Chris
Abstract: H3.3G34R/V mutations are restricted to glioblastomas of the cerebral hemispheres, and occur predominantly in adolescents and young adults. We had previously shown these mutations to result in a global re-organisation of the activating mark H3K36me3 to drive transcription of key developmental transcription factors and oncogenes such as MYCN, however the precise mechanism was unclear. Using multiple H3G34R/V samples and ChIP-seq with antibodies specific to both wild-type and mutant histone H3.3, we show a high degree of incorporation of mutant histone into nucleosomes, with only a minority (<15%) remaining wild-type only. Heterogenous G34-mutant nucleosomes displayed significantly elevated H3K36me3 binding, the majority apparently in trans to the mutation on the wild-type H3.3, and expression signatures associated with chromatin modification, cell cycle progression, DNA repair and gene transcription. Super-enhancer analysis by H3K27ac ChIP-Seq highlighted lineage-dependent transcription factors and previously identified targets MYCN and NOTCH1 (both stabilised by FBXW7, down-regulated by loss of chromosome 4q), as well as specific H3K36 lysine demethylases and splicing factors. Whole-genome CRISPR-Cas9 screening of patient-derived H3.3G34R/V cells identified critical dependencies on these latter targets, in addition to a general essentiality for genes involved in RNA processing. Assessment of RNA methylation by MeRIP-seq revealed a strong concordance of m6A-modified RNA and H3K36me3 binding, with differentially modified transcripts in mutant cellsassociated with the 3'-UTR but also the promoter and gene bodies. These data highlight the critical nature of the epitranscriptome in H3.3G34R/V-mutant paediatric glioblastoma, and highlight novel targets for therapeutic intervention.